Internationalization at Home: Seizing the Moment - Greene, Madeleine F. (International Higher Education, 2020)
A major question in the ongoing debate about the shape of higher education in the wake of COVID-19 is whether the pandemic will provide new energy and new thinking to internationalization at home (IaH). Getting unstuck will require seizing the moment, creating new language and a renewed sense of purpose, and commitment and leadership at many institutional levels.